Comparison of the Video Laryngoscopes with the Macintosh Laryngoscope for Nasotracheal Intubation in Patients Undergoing Oral and Maxillofacial Surgeries: Video Laryngoscope versus Macintosh for Nasotracheal Intubation - Zahid, Remsha; Khan, Amna; Ahmed, Faizan; Zahid, Kainaat (Pakistan Journal of Health Sciences, 2026)
Nasotracheal intubation is more desirable, whereas Macintosh may be challenging to perform in certain patients. The video laryngoscopes offer an indirect, magnified image of the glottis, which may enhance the effectiveness of intubation and shorten the length of the procedure. Objectives: To assess the video laryngoscopes and the Macintosh laryngoscopes in nasotracheal intubation of patients undergoing oral and maxillofacial surgeries. Methods: This prospective observational comparative study was done at Jinnah Postgraduate Medical Centre, Karachi, between March and August of 2023. The time of intubation, the success of the first attempt, and complications were noted. A statistical test was conducted for data analysis, and p ≤ 0.05 was regarded as significant. Results: Group A (98%) scored higher than Group B (76%) in terms of first-attempt intubation success (p=0.001). Video laryngoscopy lowered the mean intubation time (31.7 ± 3.97s) compared to Macintosh (54.7 ± 6.93s) (p=0.001). The stratified analysis showed a consistently better performance of video laryngoscopes in terms of age, gender, ASA status, BMI, and Mallampati class. Conclusions: Video laryngoscopes significantly improve first-attempt success and reduce intubation time for nasotracheal intubation in oral and maxillofacial surgery patients. Their use can enhance airway safety and procedural efficiency.